ANALISIS PENGARUH KINERJA KEUANGAN, GOOD CORPORATE GOVERNANCE, KURS DAN INFLASI TERHADAP KEMUNGKINAN FINANCIAL DISTRESS STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR KIMIA PERIODE 2013-2017 - Zamzami Rizky Rian; Halim Herman Edyanus; Efni Yulia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of financial performance proxied by profitability, solvability and activity ratio.Good corporate governance, exchange rates and inflation to financial distress in manufacturing companies basic industry chemical sector listed on Indonesia Stock Exchange for the period 2013-2017. The population in this study amounted to 65 manufacture companies listed on the Indonesian Stock Exchange with sampling techniques using purposive sampling obtained by 40 companies.The analytical method used is regression logistic analysis with process using SPSS Version 25. The results show that Profitability has a positive and significant effect on financial distress, Solvability does not have a positive significant effect on financial distress, Activity ratio does not have a positive significant effect on financial distress, Good Corporate Governance does not have a positive significant effect on financial distress, Exchange Rate does not have a positive significant effect on financial distress, Inflation does not have a negative significant effect on financial distressKeywords : Financial Performance, Good Corporate Governance, Exchange Rate, Inflation and Financial Distress.